2010
DOI: 10.1002/jrsm.5
|View full text |Cite|
|
Sign up to set email alerts
|

Robust variance estimation in meta‐regression with dependent effect size estimates

Abstract: Conventional meta-analytic techniques rely on the assumption that effect size estimates from different studies are independent and have sampling distributions with known conditional variances. The independence assumption is violated when studies produce several estimates based on the same individuals or there are clusters of studies that are not independent (such as those carried out by the same investigator or laboratory). This paper provides an estimator of the covariance matrix of meta-regression coefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1,887
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,672 publications
(1,894 citation statements)
references
References 22 publications
2
1,887
0
5
Order By: Relevance
“…Thus, if one incorporates weights based on the standard error or variance of estimates, it seems advisable to account for between study heterogeneity through random effects as discussed above and presented in columns (3) and (6). Finally, column (6) presents results applying a recently developed method that accounts for dependency among effect sizes (multiple, correlated estimates per study) (see Hedges et al 2010;Tanner-Smith and Tipton 2014). Again, results are in line with our main results, although with deflated expectations about the average effect in the whole sample of studies.…”
Section: Appendix C: Robustness Checkssupporting
confidence: 80%
“…Thus, if one incorporates weights based on the standard error or variance of estimates, it seems advisable to account for between study heterogeneity through random effects as discussed above and presented in columns (3) and (6). Finally, column (6) presents results applying a recently developed method that accounts for dependency among effect sizes (multiple, correlated estimates per study) (see Hedges et al 2010;Tanner-Smith and Tipton 2014). Again, results are in line with our main results, although with deflated expectations about the average effect in the whole sample of studies.…”
Section: Appendix C: Robustness Checkssupporting
confidence: 80%
“…Instead of arbitrarily choosing one of several tests from a RCT, we synthesized all of them and accounted for their correlations by calculating robust variance estimates. 34 The third challenge was integrating results from the various cognitive domains for detecting an overall signal regarding the cognitive effects of statins. To this end, we calculated an omnibus overall measure of cognition across all cognitive domains.…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analyses according to type of maternal diabetes (type 1 diabetes and GDM) and offspring sex were carried out. Differences between subgroups were tested for significance using metaregression: each type-specific result was treated as one study, and robust variance estimation with hierarchical weights was used to allow for dependencies between type-specific results from the same study [15]. Where studies only reported data for different types of diabetes, pooled means and SD were calculated for all diabetes types combined.…”
Section: Data Extraction and Analysismentioning
confidence: 99%